Analyzing the league of arab states and the gulf cooperation council within the framework of security regionalism in the middle east - Şen, Merve (My University, 2011)
lgesellik, Güvenlik Bölgeselliği, Arap Ligi, Körfez İşbirliği Teşkilatı, Orta Doğu. ÖZET ORTA DOĞU’DA GÜVENLİK BÖLGESELLİĞİ ÇERÇEVESİNDE ARAP LİGİ VE KÖRFEZ İŞBİRLİĞİ TEŞKİLATI’NIN ANALİZİ Bu tezin amacı Arap Ligi ve Körfez İşbirliği Teşkilatı’nı Orta Doğu’da güvenlik bölgeselliği çerçevesinde analiz etmektir. Orta Doğu diğer bölgeler ile karşılaştırıldığında genel olarak bölgesellik açısından başarısız bir örnek olarak kabul edilmektedir. Güvenlik bölgeselliği açısından ise bölge krizler, savaşlar ve düşmanlıklar ile ifade edilmektedir. Ancak bölgesel aktörler bölgede çeşitli örgütler kurmak ve işbirliğini artırmak konusunda isteklerini ortaya koymuşlardır. Bu tez Arap Ligi ve Körfez İşbirliği Teşkilatı’nın bölgesel güvenliği sağlamaktaki rollerine ışık tutmayı ve bu örgütlerin mevcut güvenlik kompleksini hangi ölçüde güvenlik topluluğuna dönüştürmeyi başardığını belirlemeyi amaçlamaktadır. Arap Ligi ve Körfez İşbirliği Teşkilatı güvenlik örgütleri olmamalarına rağmen bölgesel krizlere müdahil olmuşlar ve güvenlik konusunda çeşitli mekanizmalar oluşturmuşlardır. İşbirliğini ve böylelikle istikrar ve barışı sağlamayı amaçlayan kurumsallaşmış örgütler olmaları ve ortak kimlikleri güçlendirmeleri bu örgütlerin güvenlik topluluğu olma yolunda ilerlediklerini göstermektedir. Bölgedeki güvenlik dinamikleri ve demokratik olmayan rejimlerin varlığı bütünleşmenin daha ileri gitmesini engellemektedir. Orta Doğu’da devam eden ayaklanmalar bölgede demokratik rejimlerin kurulması ile sonuçlanırsa güvenlik topluluklarının oluşturulması söz konusu olabilecektir. Regionalism, Security Regionalism, the League of Arab States, the Gulf Cooperation Council, the Middle East.

ANALYZING THE LEAGUE OF ARAB STATES AND THE GULF COOPERATION COUNCIL WITHIN THE FRAMEWORK OF SECURITY REGIONALISM IN THE MIDDLE EAST The aim of this thesis is to analyze the League of Arab States (LAS) and the Gulf Cooperation Council (GCC) within the framework of security regionalism in the Middle East. The Middle East is widely accepted as being an anti-thesis of regionalism comparing it with the level of regionalism in other parts of the world. In terms of security regionalism, the region is described by conflicts, wars and animosities. However, regional actors showed their willingness to establish regional organizations and to promote cooperation. The objective of this thesis is to shed light on the roles of the LAS and the GCC for promoting regional security and to identify the degree to which these organizations have managed to transform existing security complex into a security community. The LAS and the GCC are not security organizations but both the LAS and the GCC have involved in regional crises and introduced various mechanisms in terms of security issues. The fact that they are institutionalized organizations which seek to assure cooperation and so stability and peace and also identities they have been promoting show that they are in the process of transforming into security communities. Security dynamics in the region and presence of non-democratic regimes hinder further integration. If the current upheavels in the region end up with the establishment of democratic regimes a path through formation of security communities can be a possible outcome.
Keywords: Bölgesellik; Körfez İşbirliği; Ortadoğu_Uluslararası İlişkiler; Uluslararası İlişkiler